Problematika Implementasi Kurikulum 2013 dalam Pembelajaran Akidah Akhlak di Madrasah Tsanawiyah Kota Prabumulih - Sunardi Sunardi; Abdurrahmansyah Abdurrahmansyah (Program Magister Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2019)
This study aims to determine the Problems in the Implementation of the 2013 Curriculum, starting from the design, implementation, and evaluation in MTs Prabumuli , then the factors underlying these problems, as well as the efforts made by teachers in overcoming the problems of implementing the 2013 Curriculum. The research approach used is a qualitative approach. While this type of research is field research. Sources of research data are the headmaster of the madrasah, deputy head of curriculum and teachers of the Akidah Akhlak. Data collection method is done by observation, interview and documentation. Data processing methods in this study were obtained through research instruments, through four stages, namely data reduction, data presentation, data verification and triangulation. The results of this study indicate that: First, the problems in implementing the 2013 curriculum in the learning of the Morals in the VII grade of MTs Prabumulih such as, 1) In planning, the making of a learning plan is not in accordance with the provisions, especially in the composition of the RPP and writing material, 2) In the implementation , the implementation of learning does not use the lesson plan as the basis of the learning flow, many learning steps that have not been done, the characteristics of the 2013 curriculum have not been fully implemented, 3) In evaluation, evaluation is still considered difficult and burdensome for teachers so that some aspects of assessment such as attitude and skills assessment are not carried out in accordance with the provisions. Second, from the above problems the factors are: 1) The lack of teacher's understanding of the 2013 curriculum concept from all aspects, 2) The teacher still considers that the 2013 curriculum is very burdensome, 3) The lack of teacher awareness in the implementation of the 2013 curriculum, 4 ) Low morale and work ethic for teachers. Third, some of the efforts made by the Akidah Akhlak teachers in overcoming existing problems such as: 1) Teachers seeking information about the 2013 curriculum concept independently, 2) Teachers play an active role in MGMP activities, 3) Collaboration with more senior teachers in the implementation of 2013 curriculum.